2012
DOI: 10.2217/pgs.11.164
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Warfarin Dosage in European–Americans and African–Americans using DNA Samples Linked to an Electronic Health Record

Abstract: Aim Warfarin pharmacogenomic algorithms reduce dosing error, but perform poorly in non-European–Americans. Electronic health record (EHR) systems linked to biobanks may allow for pharmacogenomic analysis, but they have not yet been used for this purpose. Patients & methods We used BioVU, the Vanderbilt EHR-linked DNA repository, to identify European–Americans (n = 1022) and African–Americans (n = 145) on stable warfarin therapy and evaluated the effect of 15 pharmacogenetic variants on stable warfarin dose. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
104
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(113 citation statements)
references
References 50 publications
7
104
1
1
Order By: Relevance
“…Inclusion of these SNPs in dosing models explained 41% of warfarin dose variation in African Americans, compared to only 29% explained in African Americans applying the algorithms of the International Warfarin Consortium, which was modeled in populations wherein the Black race was under-represented. 16 These data validated an earlier study by Voora et al 9 who also reported higher warfarin dose requirements in African American patients (P = 0.01) using two separate replication cohorts: one with subjects of mixed ethnicity and one consisting of African American subjects. However, while this SNP is rare in Caucasians of European descent, (allele frequency=0.002), it exhibits comparatively higher allele frequency among individuals of sub-saharan African and African American racial origin (allele frequency=0.14.)…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Inclusion of these SNPs in dosing models explained 41% of warfarin dose variation in African Americans, compared to only 29% explained in African Americans applying the algorithms of the International Warfarin Consortium, which was modeled in populations wherein the Black race was under-represented. 16 These data validated an earlier study by Voora et al 9 who also reported higher warfarin dose requirements in African American patients (P = 0.01) using two separate replication cohorts: one with subjects of mixed ethnicity and one consisting of African American subjects. However, while this SNP is rare in Caucasians of European descent, (allele frequency=0.002), it exhibits comparatively higher allele frequency among individuals of sub-saharan African and African American racial origin (allele frequency=0.14.)…”
Section: Discussionsupporting
confidence: 87%
“…The allele frequency was A (49%) and G (51%). This differed from frequencies reported in the HapMap CEU population, 10 (table 1, P <0.0001) but resembled other subpopulations of subjects from other studies with underlying cardiovascular disease conditions, 16,17 although ethnicity differed in these studies compared to the study cohort. The study cohort showed deviation from Hardy-Weinberg equilibrium (P = 0.035), while the HapMap CEU does not (P = 0.49, see table 2).…”
Section: Gene Frequenciescontrasting
confidence: 77%
See 1 more Smart Citation
“…1 In several areas of medicine, examples of the role of precision medicine in day-to-day clinical care are emerging. These include targeted approaches to treating the underlying causes of specific genetic variants in cystic fibrosis, 2 pharmacogenomic-guided methods of warfarin dosing, 3 prediction of response to clopidogrel, 4 and molecular testing of cancer patients for selection of a more targeted chemotherapy approach. 5 In contrast, the role of precision medicine in the perioperative setting (perhaps for the prevention or treatment of perioperative adverse events) has not been as widely explored.…”
mentioning
confidence: 99%
“…Ce sont notamment des approches ciblées du traitement des causes sous-jacentes de différentes variantes génétiques spécifiques de la fibrose kystique, 2 des méthodes de dosage de la warfarine guidées par la pharmacogénomique, 3 de prédiction de la réponse au clopidogrel, 4 et des tests moléculaires pour la sélection d'une chimiothérapie ciblée chez des patients cancéreux. 5 En revanche, la place de la médecine de précision dans un contexte périopératoire (pour la prévention ou le traitement d'événements indésirables périopératoires, par exemple) n'a pas été largement explorée.…”
unclassified